Welfare And Public Health Of The Population Of Russia: Adaptation To Economic Instability - Kuklin, Aleksandr Anatolyevich; Vasilyeva, Elena Vitalyevna (Economy of Regions, 2015)
In the article, the results of the research of correlation of welfare and public health of the population of Russia in the conditions of economic instability are presented. The review of performance indicators of development of public sentiments of society applied both in Russian and foreign practice is submitted. The concept content of the “social and psychological potential of a region” as an indicator of public health of the population is opened. On the basis of this concept, the potential pattern is created. The evaluation method of social and psychological potential of a region is developed, its main idea is an integrated assessment of both the potential of a region in general and its separate components. The assessment of the condition of potential in territorial subjects of the Russian Federation is given. Character and power of correlation between indicators of welfare and level of social and psychological potential of territorial subjects of the Russian Federation on the basis of development of correlation matrixes are revealed, also, the regional consistent patterns and tendencies are determined.